Hospitalization of premature infants: parents’ perceptions and revelations about nursing care - Greice Machado Pieszak; Andressa Moreira Paust; Giovana Calcagno Gomes; Andrea Moreira Arrué; Eliane Tatsch Neves; Letícia Martins Machado (Rev Rene)
Objective: to describe the perceptions of parents about the hospitalization of premature infants and the care provided by nursing staff. Methods: qualitative study in a Neonatal Intensive Care Unit with 14 parents. Medical records checking, interview with the participants and thematic content analysis were carried out. Results: parents reported surprise, fear, insecurity and guilt by hospitalization and prematurity. They mentioned as difficulties being in another city, leaving the other children and financial problems, and as facilitator factors trust and good relationship with the team and care availability. They showed fear of hospital discharge, however, they received the team’s guidelines for home care. Conclusion: hospitalization motivates different feelings related to prematurity, financial and social issues and the distance from home and families. They showed learning through the bond and trust as an important activity of the nursing staff.